SOCIALLY DISCIPLINING AND SOCIAL DRAMA IN TRADITIONAL CHILE. FLORIDA, CONCEPCIÓN , 1853-1854 - Alegría Muñoz, Paulo (Revista de Historia Social y de las Mentalidades, 2016)
The purpose of this article is to describe and analize the persistant mechanisms involved in conflict resolution that are likely to be found in traditional societies in period of republican judicial modernization. Microhistory will be used to analize a case study from a judicial record in the reduction of analytical scale. The result will show us that in rural villages, the conflict resolution mechanisms are found in ways of socially disciplining which are enforced by the civil and ecclesiastical authorities and the “community” over behaviors considered a divation from what it is expected by the hegemonic powers before its judicialization.